On the Successful Encapsulation of Water Droplets into Oil Droplets. (2015) - Chen, Xiaodong; Sun, Yingnan; Xue, Chundong; Yu, Yude; Hu, Guoqing
Abstract: Compound water-in-oil microdroplets can serve as microreactors in chemical and biological analyses. The inkjet printing is a useful technique to generate compound microdroplets by droplet impact. To understand the underlying physics during the droplet impact, a combined experimental and numerical study is carried out. The effect of spreading condition, impact velocity, and oil viscosity are investigated. The balance of the tripe-line among the three interfaces dominates primarily the stable morphology of the compound droplet. Reducing oil viscosity can reduce the required impact velocity. High impact velocity is necessary to reduce the side-slipping of the water droplet.